Subcutaneous Infection Model Facilitates Treatment Assessment of Secondary Alveolar Echinococcosis in Mice - Küster, Tatiana (Public Library of Science, 2013)
Alveolar echinococcosis (AE) in humans is a parasitic disease characterized by severe damage to the liver and occasionally other organs. AE is caused by infection with the metacestode (larval) stage of the fox tapeworm Echinococcus multilocularis, usually infecting small rodents as natural intermediate hosts. Conventionally, human AE is chemotherapeutically treated with mebendazole or albendazole. There is, however still the need for improved chemotherapeutical options. Primary in vivo studies on drugs of interest are commonly performed in small laboratory animals such as mice and Mongolian jirds, and in most cases, a secondary infection model is used, whereby E. multilocularis metacestodes are directly injected into the peritoneal cavity or into the liver. Disadvantages of this methodological approach include risk of injury to organs during the inoculation and, most notably, a limitation in the macroscopic (visible) assessment of treatment efficacy. Thus, in order to monitor the efficacy of chemotherapeutical treatment, animals have to be euthanized and the parasite tissue dissected. In the present study, mice were infected with E. multilocularis metacestodes through the subcutaneous route and were then subjected to chemotherapy employing albendazole. Serological responses to infection were comparatively assessed in mice infected by the conventional intraperitoneal route. We demonstrate that the subcutaneous infection model for secondary AE facilitates the assessment of the progress of infection and drug treatment in the live animal.